1976
DOI: 10.1007/bf01257368
|View full text |Cite
|
Sign up to set email alerts
|

Zur Pathogenese und Klinik des Magenstumpfcareinoms

Abstract: Statistics of postmortem examinations and retrospective long-term observations indicate a disposition of the resected stomach for the development of a primary carcinoma. The risk to develop a carcinoma after resection for peptic ulcer shows a two- to three-fold increase compared to gastric cancer mortality of the normal population. Because of the lack of typical symptoms for gastric stump cancer surgical treatment will occur late and the 5-years survival rate is only 1.38%. The cause of the increased cancer ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

1977
1977
1986
1986

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 13 publications
0
1
0
2
Order By: Relevance
“…Das Risiko, an einem Magencarcinom nach resezierender Ulcustherapie zu erkranken, betr~igt 8-10% und ist damit doppelt so hoch als fiJr ein vergleichbares Kontrollkollektiv Magengesunder, bei denen mit einer Erkrankungsrate von 5 % gerechnet werden muB [5,12,15]. A, tiologisch werden fiir die Carcinomentstehung im Magenstumpf unter anderem entziindlich atrophische oder metaplastische Schleim-hautver~inderungen angeschuldigt [ 12,18,21 ].…”
unclassified
“…Das Risiko, an einem Magencarcinom nach resezierender Ulcustherapie zu erkranken, betr~igt 8-10% und ist damit doppelt so hoch als fiJr ein vergleichbares Kontrollkollektiv Magengesunder, bei denen mit einer Erkrankungsrate von 5 % gerechnet werden muB [5,12,15]. A, tiologisch werden fiir die Carcinomentstehung im Magenstumpf unter anderem entziindlich atrophische oder metaplastische Schleim-hautver~inderungen angeschuldigt [ 12,18,21 ].…”
unclassified
“…Berenblum (1854) proposed a hypothetical mechanism which indicated that chemical carcinogenesis is produced through two different steps; an initiating action followed by a promotive action. In several clinical studies, the development of carcinomas was observed with a higher incidence in the resected stomach than that found in the nonoperated general population (Liavaag, 1962;Hilbe et al 1968;Kobayashi, 1970;Stalsberg and taksdal, 1971;Saegesser and jamws, 1972;Morgenstern et al 1973;Papachriston et al 1976;Peitsch and Burkhardt, 1976;Helsingen and Hillestad, 1976;Domellof and Januger, 1977). Further experimental studies have revealed that duodenogastric reflux subsequent to gastrectomy was one of the most important factors for carcinoma development in the remnant stomach (Schonlenben et al 1976;Dahm et al 1976;Meister and Schlag, 1979;Wieman et al 1980;Langhans et al 1981;Nishidoi, 1983 …”
Section: Introductionmentioning
confidence: 99%
“…Οι Peitch και Burkhardt (1976), εκ της μελέτης των βασιζόμενης επί 1659 περιπτώσεων της Διεθνούς Βιβλιογραφίας αναφέρουν ριζική ν εκτομήν 42,8 % και συμπληρωματική ν εκτομήν στομάχου 3,5 %.…”
Section: συνήθης αιματολογικός και βιοχημικός έλεγχοςunclassified